Experimental and numerical study of formation and development of disturbance waves in annular gas-liquid flow. (15th September 2020) - Fan, Wenyuan; Cherdantsev, Andrey V.; Anglart, Henryk
Abstract: Disturbance waves in a downwards annular gas-liquid flow were investigated experimentally and numerically in this study. In the experiment, the brightness-based laser-induced fluorescence (BBLIF) technique was utilized to obtain high-resolution spatiotemporal measurements for the film thickness. In the simulations, the two-phase system was simulated by the volume of fluid (VOF) method together with newly developed turbulence damping models, without which the turbulence level around the film surface is considerably under-predicted. Qualitative and quantitative comparisons were carried out for the experimental and numerical data, during which a novel method was developed to extract complex wave structures in a direct manner. Comparisons showed that the model is able to reproduce the main stages of flow evolution, including development of high-frequency initial waves, their coalesce into stable large-scale disturbance waves, generation of slow and fast ripples, and disruption of fast ripples into droplets. The main properties of modeled waves are in decent agreement with the measured ones, apart from noticeably rarer generation of ripples. The presented methods offer a new and promising option to model various energy technology systems, where annular two-phase flow occurs. Highlights: Disturbance waves in annular flow were investigated experimentally and numerically. BBLIF technique was employed to measure film thickness spatiotemporally. VOF simulations were carried out with newly developed turbulence damping models. A novel method was developed to identify different types of waves. Numerical results were validated against the experiments followed by in-depth discussions.